Composição e estrutura das assembleias de peixes de pequenos riachos afluentes do lago Ajuruxi, Mazagão-AP, Brasil - Mendes Júnior, Raimundo Nonato Gomes (Instituto Nacional de Pesquisas da Amazônia - INPA, 2013)
Surrounding terrestrial areas strongly affect the structural and limnological characteristics of small streams, directly and indirectly affecting the aquatic fauna. Thus, it is likely that different vegetation types affect the environmental characteristics and fish assemblages in headwater streams of the Amazon. This study aimed to determine 1) whether there are differences in the fish assemblages of streams in areas of the Amazon forest and savanna in the same river basin in Amapá State, and 2) how these assemblages are related to vegetation type and local environmental features of streams. We sampled 12 streams in areas of continuous forest, four in Amazonian savanna and four in forest patches in savanna. A Principal Component Analysis (PCA) was used to ordinate the environmental variables (water temperature, average depth, presence of stones in the substrate and vegetation cover). The fish assemblages were ordinated by Non-Metric Multidimensional Scaling (NMDS) based on a Sørensen dissimilarity matrix for presence-absence data, and a Bray-Curtis dissimilarity matrix for number of individuals. Relationships between composition and structure of the fish assemblages and environmental variables were tested by Analysis of Variance, Multiple Regression and Analysis of Covariance. The structure of the fish assemblages was mainly related to the size of the streams, and streams in savanna had fewer individuals and species. The composition of the fish assemblages differed between streams in different vegetation types, with two species unique to savanna streams, indicating the importance of conservation of the vegetation mosaic for the regional diversity of stream fish. The composition of the fish assemblages was related to vegetation and substrate, but the variable most associated with the fish-assemblage structure was water temperature. This indicates that changes in environmental temperature resulting from intensive land use and climate change resulting from global warming will affect the environmental characteristics of streams in the Amazon and result in changes in the composition of fish assemblages, with the risk of species extinction.
Keywords: Pequenos riachos; Fitofisionomia; Temperatura da água